Development of Manipulator ARM for Omnidirectional Mobile Past - Firdaus Bin Shahmuddin (2023)
The thesis report on the design and development of the manipulator arm of the existing ommi-directional platform. The manipulator arm is design based on the platform height and the workspace of the platform. The manipulator arm is designed to pick and drop item on the floor. These manipulator arms are made up of 4 degree of freedom and is run by using high torque servos. The entire system is controlled by using Bluetooth connectivity with Android application. Scaled down with reference to the servo capability prototype is developed.